The book of Genesis ; v. 1 - Aalders, Gerhard Charles, 1880-; Heynen, William (Grand Rapids, MI Zondervan, 1981)
Contents : v. 1 : Introduction to the Pentateuch; Introduction to Genesis; Commentary on Genesis, parts 1 and 2.
Originally published in Dutch as Het boek Genesis
Keywords: Bible. O.T. Genesis I-XVII -- commentaries